EDUCAÇÃO PERMANENTE, EM UMA UNIDADE OBSTÉTRICA, MEDIADA PELO ÁLBUM SERIADO - Xavier, Ticiana Aita (2021)
Newborn care, due to its complexity, has been a recurrent theme in Permanent Education in Health programs. The actions of promotion, prevention and assistance to newborns are of great importance, as they influence the health condition of individuals, spanning from the neonatal period to adulthood. In this direction, Permanent Education in Health, as a learning strategy at work, enables professionals to have a teaching and learning process in their daily work, mediated by critical and prospective reflection on the interprofessional work process. Under this approach, the present research had the following Objectives: to know the strategies used in training in the context of Permanent Education in Health related to newborn care; and to implement and signify the shift change as a promising learning space in an Obstetric Unit. Methodology: The steps of action research were pursued. Initially, a literature review was conducted in the National Library of Medicine, Virtual Health Library, Latin American and Caribbean Literature on Health Sciences and in the Nursing Database to identify Continuing Education strategies in Health for the qualification of care for the newborn. The intervention process, on the other hand, had as its scenario qualifying actions of newborn care during the shift change in a hospital Obstetric Unit, in a pandemic period, with the wide participation of professionals and students in the health area. Results: The newborn care intervention module in the first week of life consisted of 54 meetings held daily, right after the shift change, that is, at 1:10 pm and 7:10 pm. Health professionals and students who were joining and completing the shift participated in this process. The meetings lasted from 15 to 20 minutes, and the same theme was repeated in the different work shifts. This process was supported by the use of a flipchart, a didactic resource previously prepared by undergraduate and graduate nursing students, based on situational diagnosis, field observations and demand requested by local management. The themes covered in the flipchart are related to hygiene, skin, the newborn stump, as well as respiratory, cardiac, neurological and gastrointestinal changes. Product and its applicability: A flipchart was developed, anchored in scientific evidence and clinical knowledge. The flipchart is considered a technology of easy access and wide reach in health services, due to its practicality, dynamism and the fact that it does not depend on advanced resources for its use. The same is applicable to the various health units that provide newborn care. The development of different didactic-educational technologies should be stimulated and encouraged among health professionals, as well as among undergraduate students, in order to enable innovation and transformation of the health work process. Final considerations: The meaning of care interventions for the newborn during the shift change in a hospital Obstetric Unit revealed, for professionals and students involved in the journey, a sense of belonging, renewal and motivation for work. Providing the new in relation to teaching and learning at work implies, under this context, the ability to transcend traditional approaches and envision interactive, attractive and dynamic possibilities. It was evident that the desire for qualification and growth on the part of professionals and students involved is directly related to health intervention approaches, as well as didactic resources for support and dialogue. Training courses capable of promoting visual, auditory and kinesthetic learning are increasingly valued and required.